Le materiel informatique du CIPEA et son utilisation - Durkin, J.W.; Light, D.E.; Maehl, H.M.; Trail, J.C.M. (1984)
Examines some of the problems encountered and provides information on computer networking and the potential of computers in livestock research; describes the ILCA computer facility and the services which ILCA provides to national research organizations that do not have computer facilities.